Pengaruh Return on Asset, Earning Per Share, Price Earning Ratio Terhadap Return Saham - Laras Safira; Roy Budiharjo (LPMP Imperium, 2021)
This research aims to know the influence of Return On Asset (ROA), Earning Per Share (EPS), and Price Earning Ratio (PER) on Stock Return of Insurance company listed on the Indonesia Stock Exchange in 2013 - 2017. Data used is secondary data based on the annual report taken from the Indonesia Stock Exchange website, company website, and support sources. The technique of data analysis is multiple linear regression, which is proceeded with SPSS 21. This study uses purposive sampling and 11 of 14insurance sector companies listed in IDX used as a sample. The research result shows that Return On Asset (ROA), Earning Per Share (EPS), and Price Earning Ratio (PER) in 2013 – 2017 simultaneous and partially positive significantly affected by the stock return